2005
DOI: 10.1021/nl052038l
|View full text |Cite
|
Sign up to set email alerts
|

Two Computational Primitives for Algorithmic Self-Assembly:  Copying and Counting

Abstract: Copying and counting are useful primitive operations for computation and construction. We have made DNA crystals that copy and crystals that count as they grow. For counting, 16 oligonucleotides assemble into four DNA Wang tiles that subsequently crystallize on a polymeric nucleating scaffold strand, arranging themselves in a binary counting pattern that could serve as a template for a molecular electronic demultiplexing circuit. Although the yield of counting crystals is low, and per-tile error rates in such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
180
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(182 citation statements)
references
References 51 publications
2
180
0
Order By: Relevance
“…9 In principle, arbitrarily complex objects can be constructed using algorithmic self-assembly, 10 and objects including large finite-sized shapes and some circuit diagrams can be assembled from a small number of components. [11][12][13][14] Aperiodic one- 15,16 and two-dimensional 17,18 structures have been algorithmically self-assembled from programmable crystal monomers constructed from DNA tiles.…”
mentioning
confidence: 99%
“…9 In principle, arbitrarily complex objects can be constructed using algorithmic self-assembly, 10 and objects including large finite-sized shapes and some circuit diagrams can be assembled from a small number of components. [11][12][13][14] Aperiodic one- 15,16 and two-dimensional 17,18 structures have been algorithmically self-assembled from programmable crystal monomers constructed from DNA tiles.…”
mentioning
confidence: 99%
“…Since Winfree [19] first constructed the simple two-dimensional tiles using DNA strands to demonstrate the feasibility of computing through the self-assembling of tiles, Mao [10] came up with more complicated tiles (TX) to experimentally execute four steps of logical (cumulative XOR) operations. Barish et al [2] proposed and experimentally demonstrated an algorithmic self-assembly to perform two primitive computations: copying and counting. Fujibayashi et al [8] used tiles and DNA origami to grow crystals containing a cellular automaton pattern and proved that programmable molecular self-assembly may be sufficient to create a wide range of complex objects in one-pot reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a parallel implementation of S SS , such as a DNA implementation like those in [12,13], with 2 n seeds has at least a 1 − 1 e ≥ 0.5 chance of correctly deciding whether a B, v ∈ SubsetSum. An implementation with 100 times as many seeds has at least a 1 − 1 e 100 chance.…”
Section: Where T Is Defined Bymentioning
confidence: 99%
“…While DNA computation suffers from relatively high error rates, the study of self-assembly shows how to utilize redundancy to design systems with built-in error correction [7,8,9,10,11]. Researchers have used DNA to assemble crystals with patterns of binary counters [12] and Sierpinski triangles [13], but while those crystals are deterministic, generating nondeterministic crystals may hold the power to solving complex problems quickly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation